Pseudophylloporus Gen. nov. and Rubroleccinum Gen. nov., Two New Genera Revealed by Morphological and Phylogenetic Evidences in the Family Boletaceae from Subtropical China - Hua-Zhi Qin; Yi Wang; Wen-Fei Lin; Hui Zeng; Li-Gui Hu; Bin-Rong Ke; Zhi-Heng Zeng; Zhi-Qun Liang; Nian-Kai Zeng (Journal of Fungi)
Boletaceae, the largest and most diverse family of Boletales (Agaricomycetes and Basidiomycota), is both ecologically and economically important. Although many taxa have been described in China, the diversity of the family still remains incompletely understood. In the present study, Pseudophylloporus baishanzuensis gen. nov., sp. nov. and Rubroleccinum latisporus gen. nov., sp. nov. are proposed based on morphological and molecular phylogenetic analyses. These findings contribute to a deeper understanding of the diversity within the Boletaceae family.